IMPROVING METHODIC COMPETENCE OF PRIMARY SCHOOL MATHEMATICS TEACHERS ON SELF-DIRECTED LEARNING IN LATVIA - Sondore, Anita; Beinaroviča, Valentīna; Krastiņa, Elfrīda; Daugulis, Pēteris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
From September 2020 schools in Latvia gradually started introducing mathematics curricula and approaches in accordance with the new standards of primary education. The changes aim to prepare a competent student who is ready for self-directed learning, who is able and willing to study and solve real problems of the changing world. A competent teacher is needed to manage this individualized learning process. The research aims to find out the typical mistakes and their causes in the results of the 9th grade students' mathematics exam in Latvia, to provide support to teachers for the improvement of methodic competence of self-directed learning. To clarify the situation about mathematics studies, researchers of Daugavpils University carried out an analysis of the results of the mathematics exam in the 9th grade in the years 2015-2019 (the exam did not take place in 2020). After assessing the quality of pupils' knowledge, we can judge for which mathematics topics teachers need methodic help in the self-directed learning process in primary school. In a survey of teachers in 2018 and 2020, we sought their views on the causes of 9th grade students' mathematics exam outcomes, problems in distance learning and suggestions for methodic assistance to teachers in implementing self-directed learning. In this article we give solutions in which directions the methodic competence of primary school mathematics teachers in studies and further education should be improved.